Pengaruh kenaikan harga dan bahan bakar minyak bersubsidi terhadap pendapatan pelaku usaha angkutan kota - Gelar Pratama, Andika; Paramudhita, H. Radea Respati (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
The increase in the selling price of fuel oil has had various impacts on many aspects, one of which is the transportation sector. City transportation business actors, who are one of the business actors in the transportation sector, are directly affected by the policy of increasing fuel prices. This study analyses the effect of rising fuel prices on the income of city transport business actors in the city of Bandung. The research method used is a quantitative method with primary data obtained from distributing questionnaires to 30 city transportation drivers at the Cicaheum Terminal in Bandung City. The results of the study indicate that there is a negative and significant influence of the increase in fuel prices on the income of city transport business actors in the city of Bandung. The results of multiple linear regression analysis found a significance value of 0.400 in the price increase variable and 0.000 in the subsidised fuel oil variable, so only subsidised fuel oil has a positive influence on the income of city transport business actors in the city of Bandung. The results of this study indicate that there are limitations experienced by urban transport business actors in the city of Bandung in running their businesses as city transport drivers as a result of rising fuel prices.